PENGARUH AKHLAK BUMN DAN KOMPENSASI TERHADAP KINERJA KARYAWAN YANG DIMEDIASI EMPLOYEE ENGAGEMENT PT. PEGADAIAN KANWIL VI MAKASSAR - Atrijaya Atrijaya; Moh Hatta; Muh Ashary Anshar (Program Pasca Sarjana IBK Nitro, 2023)
This study aims to determine and analyze the effect of AKHLAK on the performance of employees mediated by PT Pegadaian Kanwil VI Makassar. This study used a quantitative descriptive method using the SPSS 26 application as a result of distributing questionnaires during the study period. The population in this study were inorganic employees of PT Pegadaian Kanwil VI Makassar and the sample in this study used a purposive sampling technique. The analytical method in this study uses Data Instrument Test, Classical Assumption Test, Multiple Linear Regression, Hypothesis Testing, Coefficient of Determination and Path Analysis. The results of this study indicate that partially the AKHLAK variable has a positive and significant effect on employee performance at PT Pegadaian Kanwil VI Makassar, AKHLAK has a positive and significant effect on employee engagement at PT Pegadaian Kanwil VI Makassar, AKHLAK indirectly has a significant effect on employee performance mediated employee engagement at PT Pegadaian Kanwil VI Makassar, compensation has a positive and significant effect on employee performance at PT Pegadaian Kanwil VI Makassar, compensation has a positive and significant effect on employee engagement at PT Pegadaian Kanwil VI Makassar, compensation indirectly has a significant effect on employee performance mediation of employee engagement at PT Pegadaian Kanwil VI Makassar and employee engagement has a positive and significant effect on employee performance.